2013
DOI: 10.1177/2047487313486040
|View full text |Cite
|
Sign up to set email alerts
|

Short-term comprehensive cardiac rehabilitation after AMI is associated with reduced 1-year mortality: results from the OMEGA study

Abstract: Attendance to early, comprehensive short-term cardiac rehabilitation programmes on top of current guideline-adjusted treatment of acute myocardial infarction is associated with a significantly improved 1-year prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 22 publications
2
76
2
6
Order By: Relevance
“…3) The baseline characteristics of the patients admitted to CR were similar as reported recently with an average age of 65 years in KARREE and 62 years of age in the OMEGA population (mostly in-patient rehabilitation) [7]. This clearly contradicts previous assumptions that ambulatory cardiovascular rehabilitation may be preferred by young patients [20].…”
Section: Discussioncontrasting
confidence: 50%
“…3) The baseline characteristics of the patients admitted to CR were similar as reported recently with an average age of 65 years in KARREE and 62 years of age in the OMEGA population (mostly in-patient rehabilitation) [7]. This clearly contradicts previous assumptions that ambulatory cardiovascular rehabilitation may be preferred by young patients [20].…”
Section: Discussioncontrasting
confidence: 50%
“…Mounting evidence suggests that exercise training alone or as core component of cardiac rehabilitation (CR) programs has several beneficial effects reducing mortality [1], preventing cardiac remodeling [2,3], and improving cardiovascular functional capacity and myocardial perfusion [4][5][6][7]. The improvement of endothelial function [8], the anti-inflammatory properties [9,10], the improvement of neurohormonal and autonomic balance [11][12][13][14][15], and the reduction of oxidative stress [16] might be some of the putative mechanisms by which exercise training exerts its beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the recent OMEGA study, which was a non-randomised cohort study, have shown that a short term comprehensive cardiac rehabilitation programme after acute MI significantly improved the 1-year prognosis (64). Those who attended rehabilitation programmes had lower allcause mortality than those who did not, but without randomised treatment assignment, interpretation of such data is difficult.…”
Section: Cardiac Rehabilitation After Acsmentioning
confidence: 98%